2019
DOI: 10.1159/000498959
|View full text |Cite
|
Sign up to set email alerts
|

Association between Plasma Levels of Growth Differentiation Factor-15 and Renal Function in the Elderly: Korean Frailty and Aging Cohort Study

Abstract: Background/Aims: Growth differentiation factor-15 (GDF-15) expression has been reported to increase in response to tissue damage and has recently emerged as a useful biomarker for various diseases. Although emerging evidence supports the clinicopathological value of GDF-15 in renal impairment, few studies have analyzed it in the elderly. Thus, we conducted a cross-sectional study to investigate the association of plasma GDF-15 with renal function and the presence of chronic kidney disease (CKD) in community-dw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
5
22
0
Order By: Relevance
“…Compared to healthy LD, we observed noticeably increased GDF15 levels in patients with ESRD. This is consistent with observations by others who found that CKD in all age cohorts leads to a significant increase of GDF15 [12,13,15,21]. In addition, GDF15 can also increase in response to acute kidney injuries [10,11].…”
Section: Discussionsupporting
confidence: 92%
“…Compared to healthy LD, we observed noticeably increased GDF15 levels in patients with ESRD. This is consistent with observations by others who found that CKD in all age cohorts leads to a significant increase of GDF15 [12,13,15,21]. In addition, GDF15 can also increase in response to acute kidney injuries [10,11].…”
Section: Discussionsupporting
confidence: 92%
“…Here we showed that serum GDF-15 levels were negatively correlated with eGFR in healthy older females. These findings are in agreement with consistent reports of association between GDF-15 and numerous risk factors and biomarkers for cardiovascular diseases [16] , [15] , [19] . Nakajima et al [16] showed that eGFR and anterior thigh muscle thickness were independent determinants of GDF-15 after adjusting for age, sex and BMI in patients with cardiovascular disease.…”
Section: Discussionsupporting
confidence: 93%
“…Nakajima et al [16] showed that eGFR and anterior thigh muscle thickness were independent determinants of GDF-15 after adjusting for age, sex and BMI in patients with cardiovascular disease. Other studies revealed that eGFR, diabetes mellitus and Hb were predictors for GDF-15 in community-dwelling older subjects [15] .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations